2006
DOI: 10.1007/s00120-005-0945-y
|View full text |Cite
|
Sign up to set email alerts
|

Hodenmetastase eines metachronen kleinzelligen neuroendokrinen Prostatakarzinoms nach Hormontherapie eines Adenokarzinoms der Prostata

Abstract: Secondary malignant testicular tumors are rare, with the exception of infiltrations by lymphomas and leukemias. Metastases are sometimes found in cancers of the lung, gastrointestinal tract, kidney, skin and prostate. Less than about 200 cases of testicular metastasis of prostate cancer have been described in the literature. This is this a very small number in comparison to the high incidence of prostate cancer and the vast number of orchiectomies for operative hormone deprivation in advanced cases. The testic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
2
0
4
Order By: Relevance
“…Hodenmetastasen eines PCa sind meist asymptomatisch und werden überwiegend zufällig durch eine Autopsie oder nach bilateraler Orchiektomie zur hormonellen Tumorsuppression bei fortgeschrittenem PCa festgestellt [ 10 ]. Es sind nur wenige klinische Fälle dokumentiert, in Deutschland wurden bisweilen nur 4 Fälle publiziert [ 2 , 7 – 9 ]. In der Literatur wird über verschiedene mögliche Metastasierungswege diskutiert: retrograd venös, retrograd lymphatisch, arteriell embolisch, retrograd über den Ductus deferens oder durch direkte Ausbreitung [ 7 ].…”
Section: Diskussionunclassified
“…Hodenmetastasen eines PCa sind meist asymptomatisch und werden überwiegend zufällig durch eine Autopsie oder nach bilateraler Orchiektomie zur hormonellen Tumorsuppression bei fortgeschrittenem PCa festgestellt [ 10 ]. Es sind nur wenige klinische Fälle dokumentiert, in Deutschland wurden bisweilen nur 4 Fälle publiziert [ 2 , 7 – 9 ]. In der Literatur wird über verschiedene mögliche Metastasierungswege diskutiert: retrograd venös, retrograd lymphatisch, arteriell embolisch, retrograd über den Ductus deferens oder durch direkte Ausbreitung [ 7 ].…”
Section: Diskussionunclassified
“…Although the testicles are considered to be an inhospitable environment for cancer cells due to the low temperature, rarely neoplastic cells are able to invade them through the systematic venous, lymphatic circulation, or direct tumor invasion [ 14 ]. Although testicular metastases from other solid tumors have been rarely described, it is known that prostate cancer is the commonest primary tumor with such a predilection [ 15 , 16 ]. In this paper, we presented the fourth case of a CUP patient diagnosed with a metastatic scrotal lesion (see Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In 2004 Salesi et al reported a case of a 62-year-old man who presented with dyspnea, while a testicular mass and lung metastases with pleural effusion were noted. The final diagnosis according to the IHC studies was occult gastrointestinal adenocarcinoma [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Es kann davon ausgegangen werden, dass auch die "BlutHoden-Schranke" eine gewisse Metastasierungsbarriere darstellt, weshalb es nur in seltenen Fällen zu einer testikulä-ren Metastasierung kommt. Insbesondere bei ungewöhnlichen duktalen, neuroendokrinen oder kleinzelligen Karzinomen scheint eine Hodenmetastase durchaus möglich und sollte differenzialdiagnostisch bedacht werden [6].…”
Section: Diskussionunclassified